Barriers and Potential Solutions for Energy Renovation of Buildings in Denmark - Niels I Meyer; Brian Vad Mathiesen; Frede Hvelplund (International Journal of Sustainable Energy Planning and Management, 2014)
Buildings account for a substantial part of the total energy consumption. In Denmark this number is about 40 % and this is approximately the same in most industrial countries. On this background there is an urgent need to develop strategies for reducing the energy demand in the building sector. Renovation of existing buildings must have high priority as houses often last for 50 to 100 years, while the time perspective for the desired transformation to low-energy houses is less than 30 years in order to mitigate global warming and avoid irreversible tipping-points. The only sustainable energy supply in the perspective of centuries is renewable energy provided by the sun and exploited in the form of solar heat, solar electricity (PVs), wind power, hydropower, wave power, and some types of biomass etc. A future dominating role of intermittent renewable sources requires new integrated systems thinking on both the supply and demand side for heat, electricity and transport. Implementing such Smart Energy Systems requires integrated strategic energy planning on the national and local level. With the fundamental changes in the energy supply technologies expected during the coming years, it is important to synchronize investments in energy conservation measures with investments in the supply side, in order to avoid overinvestment in supply systems and thus to minimize the total costs of the transformation to Smart Energy Systems. This paper highlights some of the most important barriers for renovation of existing buildings in Denmark and points to policies for overcoming these barriers.